2006
DOI: 10.1001/jama.296.8.974
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Pressure Ulcers: A Systematic Review

Abstract: Given current evidence, using support surfaces, repositioning the patient, optimizing nutritional status, and moisturizing sacral skin are appropriate strategies to prevent pressure ulcers. Although a number of RCTs have evaluated preventive strategies for pressure ulcers, many of them had important methodological limitations. There is a need for well-designed RCTs that follow standard criteria for reporting nonpharmacological interventions and that provide data on cost-effectiveness for these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
490
2
57

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 702 publications
(557 citation statements)
references
References 83 publications
8
490
2
57
Order By: Relevance
“…These guidelines show strong evidence for using a low interface pressure mattress rather than a normal mattress with patients at risk of developing PUs (19) . Specialized support surfaces (such as mattresses, beds and pillows) help reduce or relieve the pressure that the weight of the body of the patient has on the skin and subcutaneous tissues when they are pressed against the surface of the bed or chair (20) .…”
Section: Results Regarding the Preventive Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…These guidelines show strong evidence for using a low interface pressure mattress rather than a normal mattress with patients at risk of developing PUs (19) . Specialized support surfaces (such as mattresses, beds and pillows) help reduce or relieve the pressure that the weight of the body of the patient has on the skin and subcutaneous tissues when they are pressed against the surface of the bed or chair (20) .…”
Section: Results Regarding the Preventive Measuresmentioning
confidence: 99%
“…The aim of the repositioning and of the support surfaces is to reduce or eliminate the interface pressure and, thus, to improve the microcirculation in the regions of the body that are at risk (20) . The change in decubitus position and hydration of the skin of patients at risk for PU depend solely on the nurse making the prescription and the implementation of it by the nursing team.…”
Section: Results Regarding the Preventive Measuresmentioning
confidence: 99%
“…Three were found, however these were not restricted to ENT, and/or did not perform extensive searches in databases, and/or had not been properly updated. The first review (16) included eight studies that dated from 1971 to 1995, the second (17) had four from 1990 to 2002, and the third (18) had seven studies from 1971 to 2006. In this review ten studies published between 1971 to 2012 were included, of which five had more recent publication years to the other reviews.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, an SR evaluating treatments available for PU nutritional interventions included seven RCTs and the authors found that the protein supplementation promoted the healing of ulcers compared with placebo (Scale Healing average score 3.55 [4.66] vs. 3.22 [4:11], p <0.05), but there is little evidence to justify routine use of ENT compared to the standard treatment for PU healing (18) .…”
Section: Introductionmentioning
confidence: 99%
“…Pressure ulcer prevention requires regular follow-up to identify changes in clinical status and daily skin inspections to detect early evidence of pressure-induced skin damage [142]. For high-risk individuals, regular turning and repositioning schedule with particular attention to vulnerable tissue covering bony prominences are recommended [143]. Sufficient staffing levels are necessary for effective pressure ulcer prevention [144].…”
Section: Pressure Ulcersmentioning
confidence: 99%